Antioxidant and Acetylcholinesterase Inhibitory Potential of Thai Medicinal Plants - Kasempitakpong, Boonsong; Kusirisin, Winthana; Jaikang, Churdsak; Sermpanich, Nipon (Current Nutrition & Food Science, 2015)
Inhibition of acetylcholinesterase (AChE) and prevention of acetylcholine degradation are of the most accepted therapies for Alzheimer’s disease. Aqueous extracts of seventeen Thai medicinal plants were used in traditional Thai medicine for preventing chronic diseases such as diabetes, hypertension and cardiovascular diseases. They were tested for cholinesterase inhibitory properties using the Ellman’s colorimetric method. The extracts were screened for their free radical scavenging properties using 1, 1 diphenyl-2-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP) and metal chelating method. Total phenolic, total flavonoid, total tannin and total alkaloids contented in the extracts were determined. The results found that Cassia siamea (CS) was the most potent inhibitor of AChE activity with IC50 value 0.85±0.06 mg/ ml. Lagerstroemia speciasa (LS) had the highest potency to scavenge DPPH radical with 50% scavenging concentration (SC50) value 0.27±0.01 mg/ ml. CS and LS were high in reducing Fe3+ to Fe2+ with values 1.22± 0.06 and 1.49±0.02 mM of Fe2+ equivalent, respectively. 1 mg/ml of CS was the highest potency to inhibit AChE activity with 58.83±2.24%. Results showed AChE inhibition ability depended on the amount of total phenolic content. This study highlights CS extract which showed highly potent inhibition of AChE and scavenging of free radicals. Clinical trials and active compounds in CS should be studied for AD therapy in the other models.
Keywords: free radical scavenging